Impulsive Markov jump linear systems: Stability analysis and H2 control. (November 2021) - Souza, Matheus; Fioravanti, André R.; Araujo, Vanessa S.P.
Abstract: In this work, we present an impulsive Markov jump linear system model. We show how the present model generalises previous works from the literature, and we devise necessary and sufficient conditions for stability and performance, together with mode-dependent state-feedback control design conditions for such systems. An applied example shows how the developed theory can be used to control strategies under actuator and sensor failures.